Chromatin-associated noncoding RNAs in development and inheritance - Acharya, Sreemukta; Erhardt, Sylvia (Wiley interdisciplinary reviews. RNA, 2017)
Noncoding RNAs (ncRNAs) have emerged as crucial players in chromatin regulation. Their diversity allows them to partake in the regulation of numerous cellular processes across species. During development, long and short ncRNAs act in conjunction with each other where long ncRNAs (lncRNAs) are best understood in establishing appropriate gene expression patterns, while short ncRNAs (sRNAs) are known to establish constitutive heterochromatin and suppress mobile elements. Additionally, increasing evidence demonstrates roles of sRNAs in several typically lncRNA-mediated processes such as dosage compensation, indicating a complex regulatory network of noncoding RNAs. Together, various ncRNAs establish many mitotically heritable epigenetic marks during development. Additionally, they participate in mechanisms that regulate maintenance of these epigenetic marks during the lifespan of the organism. Interestingly, some epigenetic traits are transmitted to the next generation(s) via paramutations or transgenerational inheritance mediated by sRNAs. In this review, we give an overview of the various functions and regulations of ncRNAs and the mechanisms they employ in the establishment and maintenance of epigenetic marks and multi-generational transmission of epigenetic traits. WIREs RNA 2017, 8:e1435. doi: 10.1002/wrna.1435 This article is categorized under: RNA Interactions with Proteins and Other Molecules > Protein-RNA Interactions: Functional Implications Regulatory RNAs/RNAi/Riboswitches > Regulatory RNAs RNA in Disease and Development > RNA in Development
Gesehen am 02.10.2018